Enhancing Global Service-Learning with Partnerships as an Engagement Strategy for Christian Higher Education. Issue 5 (19th October 2016) - Bish, Gregory T.; Lommel, John
ABSTRACT: Global engagement programming across higher education continues to expand as institutional leaders and practitioners strive to meet global citizenship and civic engagement outcomes. This article presents case study research on a global service-learning partnership, the "Christian University" (CU) Wheelchair Project, which has involved students in a three-semester course sequence that includes research under faculty guidance at a Kenyan school serving 300 children with disabilities. The coauthors participated with the CU students to address the following research questions: (a) What are the characteristics of a Christian Global Service-Learning project that involved partnerships? and (b) What are the observed expectations and impacts of this partnership in the local setting? The case study offers an example of a global service-learning partnership that is grounded in institutional and community input throughout the project's conception and implementation, as well as during assessment of the program. Analysis of the data revealed three components of this program as an effective model of a global service-learning partnership: (a) shared representation throughout the program, (b) valuing both student and community outcomes, and (c) additional perceived community benefits. Corbett and Fikkert's (2012 ) relief-rehabilitation-development and Fraser's (2009 ) parity of participation frameworks were used to illustrate why it is necessary to intentionally develop partnerships where the local community can genuinely participate. Drawing from the related literature, the authors argue that global service-learning with partnership programs have the potential to move Christian higher education beyond simply service to transformative and sustained community collaboration in which social justice can be effectively enacted.